«Russian and foreign experience of municipal management of the social sphere in the digital environment» ("Journal "U". Economy. Management. Finance.", 2023)
Economics and management are currently changing significantly and rapidly, transforming from traditional diverse forms into a variety of digital ones. Innovative opportunities for data accumulation, analysis and processing are emerging. Digital trends are increasingly being introduced into public and government sectors. There is also a process of digitalization of public administration. This process is uneven, with different levels of government digitalization in different countries. Modern digital technologies provide absolutely new opportunities for the government to interact with citizens and meet their various needs through the provision of public services. This, in turn, requires new competencies, knowledge, and skills from civil servants. Digitalization of the economy and society is changing the organization, functional strategy and corporate culture. Digital technologies are used in public administration to achieve qualitative breakthroughs in management processes, which leads to sustainable economic growth. The article reveals examples of the development of digitalization in the UK, USA, Australia, Germany, the Scandinavian countries and Southeast Asia, which are considered the most successful from the point of view of monitoring international assessments in the development, application of information technologies, digitalization of the national economy. The level of development of digital technologies in the field of municipal administration and the place of Russia in the implementation of digital economy policy, as well as the economic essence and principles of digital transformation of the social sphere as an object of research and its current state are shown.
Keywords: digitalization; state and municipal administration; digital technologies; digital opportunities; social sphere; management efficiency; global digital transformation; global digitalization; digital development of national economies